(Analysis of Children's Cognitive Abilities Through Web-Based Educational Games at TKN Pembina Gondang) - Alawiyah, Tuti; Rahayu, Eka Pamuji (JUPE : Jurnal Pendidikan Mandala, 2024)
This research is motivated by the use of games which are inseparable from the world of children, it could even be said to be very important for the growth of children's intelligence, the importance of these games is that wherever they are, both at home and in the school environment, various games are now available for children so that the aim of This research is 1) to analyze children's cognitive abilities through web-based educational games and 2) the impact of these games on children's cognitive abilities. The location of this research is TKN Pembina Gondang which is located in the North Lombok area using research methods, namely using qualitative research with a case study approach and the data obtained is analyzed using data analysis, namely data transcription, data reduction, data validation or triangulation, presentation. data and drawing conclusions. So the research results obtained are: 1) The use of web-based educational games is able to influence the cognitive abilities of young children, especially in the aspects of problem solving, logical thinking and symbolic thinking; 2) The use of web-based educational game media, especially Wordwall Net, has a positive impact on children's cognitive abilities, because through this game children behave in a way that shows curiosity, have initiative in choosing games, are able to solve problems creatively, use number symbols to calculate, follow the rules, and be able to use technology correctly.